Implementation of a Mental Health Care Website for Psychological Counseling and Education Based on Spring Boot and Tailwind CSS - Yosua Christian Prasetio; Yeremia Alfa Susetyo (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The increasing demand for mental health services among young people in Indonesia is not matched by adequate accessibility due to constraints related to time, cost, and social stigma. This study aims to implement a